The fretting fatigue performance of Ti–6Al–4V alloy influenced by microstructure of CuNiIn coating prepared via thermal spraying. (May 2020) - Ma, Amin; Liu, Daoxin; Zhang, Xiaohua; He, Guangyu; Liu, Dan; Liu, Chengsong; Xu, Xingchen
Abstract: Two types of CuNiIn coatings with different microstructures were successfully prepared on the surface of a Ti–6Al–4V alloy by means of high-velocity oxygen fuel (HVOF) and plasma spray (PS), respectively. The effect of the coating microstructure on the fretting fatigue (FF) resistance of the alloy as well as crack initiation and propagation was investigated. Compared with the HVOF-CuNiIn coating, the PS-CuNiIn coating was composed of a more significant lamellar microstructure and exhibited higher FF resistance. HVOF-CuNiIn possessed low resistance to crack initiation due to its low toughness, thus leading to a short FF life of the titanium alloy. The excellent FF resistance of the rotary flay peening (RFP)-treated sample resulted mainly from the large value of the compressive residual stress. Highlights: The PS-CuNiIn coating and HVOF-CuNiIn coating presented different microstructure. PS coating improved FF life of Ti6Al4V whereas HVOF coating decreased its FF life. Lamellar microstructure of PS coating was benefit to control cracks propagation. The RFP and PS combined treatment yielded a high FF life.